2016
DOI: 10.1177/0022034516679973
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides: Mechanisms of Action and Resistance

Abstract: More than 40 antimicrobial peptides and proteins (AMPs) are expressed in the oral cavity. These AMPs have been organized into 6 functional groups, 1 of which, cationic AMPs, has received extensive attention in recent years for their promise as potential antibiotics. The goal of this review is to describe recent advances in our understanding of the diverse mechanisms of action of cationic AMPs and the bacterial resistance against these peptides. The recently developed peptide GL13K is used as an example to illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
407
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 523 publications
(450 citation statements)
references
References 56 publications
5
407
0
9
Order By: Relevance
“…Interestingly, a clear separation in the disposition of the two sets of residues was noted, with all the positively-charged side chains converging towards one side of the peptide (Figure 9c). This observation complies with the hypothesis that these peptides assume an amphipathic 3D conformation [2], with a charged region responsible for binding to the negatively-charged LPS on the surface of Gram negative bacteria, and a predominantly hydrophobic nature allowing the peptide to then penetrate the membrane. The surface of the centroid VCP-VT1 was also analysed in terms of polarity, and a clear distinction between hydrophilic and hydrophobic areas could be observed (Figure 9d), in accordance with what was discussed for the peptides with experimentally-known conformations.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, a clear separation in the disposition of the two sets of residues was noted, with all the positively-charged side chains converging towards one side of the peptide (Figure 9c). This observation complies with the hypothesis that these peptides assume an amphipathic 3D conformation [2], with a charged region responsible for binding to the negatively-charged LPS on the surface of Gram negative bacteria, and a predominantly hydrophobic nature allowing the peptide to then penetrate the membrane. The surface of the centroid VCP-VT1 was also analysed in terms of polarity, and a clear distinction between hydrophilic and hydrophobic areas could be observed (Figure 9d), in accordance with what was discussed for the peptides with experimentally-known conformations.…”
Section: Discussionsupporting
confidence: 86%
“…To this aim, a library of active peptides with known 3D structures was initially created and clustered and the centroids analyzed. This confirmed the experimental evidence that the majority of these molecules often contain basic amino acid residues in close proximity to aromatic residues and that they assume an amphipathic conformation [2,5]. Furthermore, it was shown that their predicted conformations are in excellent agreement with those experimentally observed in solution.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…They have been classified for shared properties that appear to be important for their structure and activity such as their cationic amphipathic character, regions rich in hydrophobic and aromatic residues1314 or intra-chain cystine bonds as described for defensins15 and protegrins16. Whereas a good number of sequences carrying such intra-chain cystine bridges have been described151617, dimeric peptides with inter-chain disulfide bonds are less common with the heterodimeric peptide distinctin being the only example published so far18.…”
mentioning
confidence: 99%
“…Furthermore, the limitations of conventional antibiotics in the treatment of periodontal disease are well known, especially that of the bacterial resistance induction (Herrera, Alonso, LeĂłn, RoldĂĄn, & Sanz, ). Hence, the development of new therapeutic molecules reproducing AMP functions is particularly appealing considering that it involves low cytotoxicity and no bacterial resistance (Bechinger & Gorr, ; Helmerhorst et al., ; Peters, Shirtliff, & Jabra‐Rizk, ).…”
Section: Discussionmentioning
confidence: 99%